2004
DOI: 10.1158/0008-5472.can-03-3773
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Gene, C13orf25 , as a Target for 13q31-q32 Amplification in Malignant Lymphoma

Abstract: The amplification at 13q31-q32 has been reported in not only hematopoietic malignancies but also in other solid tumors. We identified previously frequent amplification of chromosomal band 13q31-q32 in 70 cases of diffuse large B-cell lymphoma patients by conventional comparative genomic hybridization analysis. In an attempt to identify a candidate gene within this region, we used array comparative genomic hybridization and fluorescent in situ hybridization to map the 13q31-q32 amplicon. We then screened the 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
577
1
19

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 703 publications
(605 citation statements)
references
References 33 publications
8
577
1
19
Order By: Relevance
“…Of these, only MIR17HG has been previously associated with tumorigenesis; it is included in the 13q31 5 amplicon in lymphoma. 13 The only microdeletions identified in this study resulted in loss of CDKN2A in four cases and ETV6 in one case (Supplementary Table 1), corresponding to a mean of 0.42 microdeletions per case. This is a relatively low frequency compared with other subtypes of BCP ALL 14 and could be due to the fact that the leukemic cell has already lost massive amounts of genetic material; additional deletions may therefore not be necessary for leukemogenesis or be incompatible with cell viability.…”
mentioning
confidence: 74%
“…Of these, only MIR17HG has been previously associated with tumorigenesis; it is included in the 13q31 5 amplicon in lymphoma. 13 The only microdeletions identified in this study resulted in loss of CDKN2A in four cases and ETV6 in one case (Supplementary Table 1), corresponding to a mean of 0.42 microdeletions per case. This is a relatively low frequency compared with other subtypes of BCP ALL 14 and could be due to the fact that the leukemic cell has already lost massive amounts of genetic material; additional deletions may therefore not be necessary for leukemogenesis or be incompatible with cell viability.…”
mentioning
confidence: 74%
“…The miR-17-92 cluster is frequently amplified in several lymphomas and in lung cancer, 16,42 and aberrant overexpression of the miR-17-92 polycistron is detected in many cancers. 43 Retinoblastoma-like 2 protein (p130, Rbl2), Cdk inhibitor p21CIP1, transforming growth factor β1 (TGFβ1), proapoptotic Bcl-2 protein Bim, the tumor-suppressor PTEN and transcription factor E2F1 are some of the cluster's targets.…”
Section: Discussionmentioning
confidence: 99%
“…The most comprehensively studied example of an miRNA locus with these properties is the mir-17 cluster, consisting of six miRNAs: miRs- 17-5p, -18, -19a, -19b, -20, and -92. This miRNA cluster is located on human chromosome 13q31, a region that is frequently amplified in several types of lymphoma and solid tumours (Ota et al, 2004). In a recent study, He et al (2005) found that miRNAs from this cluster are highly expressed in B-cell lymphoma samples and cell lines.…”
Section: Proproliferative/antiapoptotic Mirnasmentioning
confidence: 99%